Comparison of thresholding techniques for extraction of electrical hotspots from infrared images - Abir, Asaduzzaman; Joy, Md. Rifat Islam; Fuad, Mobtasim; Emon, Nafiul Ahmed (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.